The Legal Force of the International Court of Justice Decision on the Appeals Dispute: (Case Study: ICJ Decision No. 173 on the Appeals Dispute between Bahrain, Saudi Arabia, Egypt, and the UAE versus Qatar) - Hafina Haula Arsy; Risnain, Muh; Guna Nugraha, Lalu (Mataram Journal of International Law, 2023)
The Statute of the International Court of Justice does not include provisions regarding the authority or jurisdiction of the International Court to handle appellate cases. However, in practice, the International Court of Justice has issued judgments on appeals related to the ICAO Council's jurisdiction in disputes over flight restrictions in Qatar imposed by Bahrain, Egypt, Saudi Arabia, and the United Arab Emirates (UAE). This study aims to analyze the nature of decisions related to these appellate disputes. The research methodology employed is normative research with a legislative, conceptual, and case study approach. The findings of this research indicate that decisions on appellate cases are deemed final and binding as stipulated in Article 60 of the Statute of the International Court of Justice and Article 86 of the Chicago Convention, and the obligation of UN member states to comply with the judgments of the International Court of Justice is regulated in Article 94 of the United Nations Charter.